Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physreva.84.012331
|View full text |Cite
|
Sign up to set email alerts
|

State protection under collective damping and diffusion

Abstract: In this paper we provide a recipe for state protection in a network of oscillators under collective damping and diffusion. Our strategy is to manipulate the network topology, i.e., the way the oscillators are coupled together, the strength of their couplings, and their natural frequencies, in order to create a relaxation-diffusion-free channel. This protected channel defines a decoherence-free subspace (DFS) for nonzero-temperature reservoirs. Our development also furnishes an alternative approach to build up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Previous works on dissipative harmonic oscillators reported that in presence of identical frequencies and couplings between oscillators the symmetry of the collective motion and their interaction with the environment can lead to the effective decoupling of some of the normal modes of the system from the bath [24][25][26][27][28]. The cases of different frequencies [29,30] or couplings [31] is instead less studied and understood. The natural step of considering three harmonic oscillators beyond the symmetric configuration of identical oscillators already provides much more phenomenological richness while at the same time it allows for analytic treatment and gives valuable intuition when pursuing a further extension to the case of N oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works on dissipative harmonic oscillators reported that in presence of identical frequencies and couplings between oscillators the symmetry of the collective motion and their interaction with the environment can lead to the effective decoupling of some of the normal modes of the system from the bath [24][25][26][27][28]. The cases of different frequencies [29,30] or couplings [31] is instead less studied and understood. The natural step of considering three harmonic oscillators beyond the symmetric configuration of identical oscillators already provides much more phenomenological richness while at the same time it allows for analytic treatment and gives valuable intuition when pursuing a further extension to the case of N oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the inescapable sources of noise and decoherence in the quantum evolution make the production of long-lived quantum states considerably challenging [8]. Nowadays, substantial efforts have been devoted to promote efficient techniques for preparing and protecting nonclassical states from quantum noise [9,10], for instance, decoherence-free subspaces [11,12], dynamical decoupling [13], and reservoir engineering [14][15][16], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The development of strategies to prepare nonclassical states [4] and, particularly, to circumvent their decoherence has long been a challenge in quantum information studies. Despite this, important efforts have been proposed to overcome this obstacle , e.g., via decoherence-free subspaces [5,6], dynamical decoupling [7], and reservoir engineering [8,9]. From the conceptual viewpoint, the need for these states stems from their use in the study of fundamental quantum processes, such as decoherences [10] and quantum-to-classical transitions [11].…”
Section: Introductionmentioning
confidence: 99%